Promoting Sustainable Tourism Entrepreneurship in Indonesian Local Communities: Challenges and Opportunities - Anisa, Nurul; Margy Ariana, Patricia; Ramadhani, Alfi (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
Sustainable tourism is becoming an important issue in economic development and environmental conservation in Indonesia. Local communities have a key role in promoting sustainable tourism entrepreneurship to achieve sustainable development goals. This research aims to understand the challenges and opportunities faced by Indonesian local communities in promoting sustainable tourism entrepreneurship. The research method used is descriptive qualitative involving case studies in several tourism sites in Indonesia. Data were collected through in-depth interviews with key stakeholders, participatory observation, and analysis of relevant documents. The research also adopted a triangulation approach to enhance data validity. The results show that Indonesian local communities face complex challenges in promoting sustainable tourism entrepreneurship. These include a lack of understanding of the concept of sustainable tourism, a lack of entrepreneurial skills, a lack of access to capital and technology, and limited support from the government and relevant institutions. However, the study also identified a number of opportunities that local communities can take advantage of, including Indonesia's rich culture and nature, the increasing interest of tourists in sustainable tourism, as well as the active role of non-governmental organizations and the private sector in promoting sustainable tourism entrepreneurship.